Battlestar Galactica and international relations - Neumann, Iver B.; Kiersey, Nicholas J. (Popular culture and world politics, 2013)
"Tackling some of the key contemporary issues in IR, the writers of BSG have taken on a range of important political themes and issues, including the legitimacy of military government, the tactical utility of genocide, and even the philosophical implications of artificial intelligence technologies for the very category of what it means to be 'human'. The contributors in this book explore in depth the argument that one of the most important aspects of popular culture is to naturalize or normalise a certain social order by further entrenching the expectations of social behaviour upon which our mentalities of rule are founded"--